2016
DOI: 10.1155/2016/5945192
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Accuracy of Classical Machine Learning Antispam Classifiers in Real Scenarios by Applying Rough Set Theory

Abstract: Nowadays, spam deliveries represent a major problem to benefit from the wide range of Internet-based communication forms. Despite the existence of different well-known intelligent techniques for fighting spam, only some specific implementations of Naïve Bayes algorithm are finally used in real environments for performance reasons. As long as some of these algorithms suffer from a large number of false positive errors, in this work we propose a rough set postprocessing approach able to significantly improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…5 and Fig. 9 examine the outcomes of classification analysis for MOMBD-CDD method upon the applied ECUE spam dataset [26][27][28][29]. The table values correspond that the HELF technique resulted in minimum accuracy of 75%.…”
Section: Dataset Usedmentioning
confidence: 90%
“…5 and Fig. 9 examine the outcomes of classification analysis for MOMBD-CDD method upon the applied ECUE spam dataset [26][27][28][29]. The table values correspond that the HELF technique resulted in minimum accuracy of 75%.…”
Section: Dataset Usedmentioning
confidence: 90%
“…Table 5 and Fig. 14 computes a detailed comparative results analysis of the CIDD-ADODNN model on the test Spam dataset [23][24][25]. The resultant scores reported that HELF and KNN models have depicted inferior performance by obtaining lower accuracy values of 0.750 and 0.818, respectively.…”
Section: Performance Validationmentioning
confidence: 99%
“…The text mining research field (Tandel, Jamadar, & Dudugu, 2019) emerged as the prevalent form of exploiting token information to solve problems such as text classification, information retrieval, etc. Furthermore, the first well-known ML proposal for spam filtering 4 introduced by Paul Graham, and many others introduced later (Méndez, Glez-Peña, Fdez-Riverola, Díaz, & Corchado, 2009;Pérez-Díaz, Ruano-Ordás, Fdez-Riverola, & Méndez, 2016), take advantage of token-based information. In this manner, topic models (Grün & Hornik, 2011) emerged with the aim of studying terms that are usually found together in texts and therefore allow for topic detection without using semantic information about the connections between terms.…”
Section: Related Workmentioning
confidence: 99%